EP1168 The influence of obesity on tumor recurrence in vulvar cancer patients. (1st November 2019) - Klapdor, R; Hillemanns, P; Wölber, L; Jückstock, J; Hilpert, F; de Gregorio, N; Hasenburg, A; Sehouli, J; Fürst, ST; Strauß, HG; Baumann, K; Thiel, F; et al.
Abstract : Introduction/Background: Obesity is associated with decrased survival in several cancer entities. The influence of obesity on prognosis of vulvar cancer patients is not clear. However, knowledge about this may have consequences on treatment and follow-up. Methodology: This is an analysis of the large AGO-CaRE-1 study which included vulvar cancer patients (UICC stage IB and higher), treated in 29 cancer centers between 1998 and 2008, in order to analyze treatment patterns and prognostic factors. Results: In total, 849 eligible patients were divided into two groups depending on their body mass index (BMI, <30 vs. ≥30 kg/m²). We did not detect differences in the baseline variables (age, tumor diameter, depth of infiltration, tumor stage, nodal invasion, tumor grade) and treatment variables (R0 resection, chemotherapy, radiotherapy and continuation of adjuvant therapy) between both groups (p>0.05). Radical vulvectomies were performed more frequently in patients having a BMI ≥30 kg/m² (61.1% vs. 51.8%, p=0.042). Interestingly, we detected a higher recurrence rate in the group having a BMI ≥30 kg/m² (43.4%, vs. 28.3%, p<0.01) due to an increased rate of local recurrences (33.3% vs. 18.5%, p<0.01). This led to significantly shorter disease free survival of obese patients in univariate analysis (HR 1.362, 95%CI 1.093–1.696, p=0.006) and multivariate Cox-regression analysis (BMI <30 kg/m² vs. ≥30 kg/m², HR 1.811, 95%CI 1.005–3.262, p=0.048). Noteworthy, this association was not linear: in an additional subgroup analysis on five BMI groups we detected a longer time to recurrence in women with a slightly increased BMI 25–30 kg/m² compared to those with a normal BMI between 19 and 25 kg/m² (OR 0.55, 95%CI 0.33–0.91, p=0.02). Conclusion: In this first large study about the association between obesity and prognosis of vulvar cancer patients, we observed that a BMI ≥30 kg/m² was associated with shorter DFS, mainly attributed to a higher risk for local recurrence. Disclosure: Conflicts of Interest and Source of Funding: All authors declare that there are no conflicts of interest involved with the presented data. The CaRE-1 study was supported by medac oncology without restriction in protocol or analysis